2019
DOI: 10.15389/agrobiology.2019.5.1052eng
|View full text |Cite
|
Sign up to set email alerts
|

PRE-SOWING PROTECTION OF INOCULATED SOYBEAN Glycine max (L.) Merr. SEEDS BY WATER-SOLUBLE POLYMER COMPOSITIONS AND THEIR SOLID-PHASE MODIFICATION

Abstract: Водорастворимые полимеры в качестве прилипателей и пленкообразователей обеспечивают лучшую адгезию бактерий на семенах (по типу многокомпонентных формуляций при производстве современных химических протравителей). В этом качестве испытывались альгинат натрия низкой и высокой молекулярной массы (FMC полимер), гидроксипропилметилцеллюлоза (HPMC) (Colorcon®, «Colorcon, Inc.», США), полиэтиленгликоль (ПЭГ, PEG), карбомер (карбопол), поливиниловый спирт (PVA) и поливинилпирролидон (повидон, PVP). Более того, как ока… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…In the study of survival of 634b strain on the 'Belgorodska 7' (creator -Federal State Budgetary Educational Institution of Higher Education "V. Gorin Belgorod State Agricultural University", Russia) soybean variety seeds under the influence of polymers of different origin and composition it was shown that polyvinylpyrrolidone 10 % solution is the most effective of these compounds. Its use ensures the preservation of 10 times more number of viable rhizobia on the seeds in 10 days after inoculation compared to control (Laktionov et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the study of survival of 634b strain on the 'Belgorodska 7' (creator -Federal State Budgetary Educational Institution of Higher Education "V. Gorin Belgorod State Agricultural University", Russia) soybean variety seeds under the influence of polymers of different origin and composition it was shown that polyvinylpyrrolidone 10 % solution is the most effective of these compounds. Its use ensures the preservation of 10 times more number of viable rhizobia on the seeds in 10 days after inoculation compared to control (Laktionov et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Such seeds can be sown without the need for inoculation on the farm, which is a time-consuming procedure (Pedrini et al, 2017). Laktionov et al (2019) reported that the use of certain polymers for seed coating increased the survival rate of rhizobia more than 10-fold, which had significant practical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Досліджували також низку водорозчинних полімерів (альгінат натрію, поліетиленгліколь, карбомер, полівініловий спирт, полівінілпіролідон та ін.) як речовини, добавляння яких у різні формуляції біопрепаратів може підвищити стійкість мікробних агентів до хімічних ЗЗР, УФ-випромінювання, перепадів температур та висихання і тим самим забезпечити ліпшу виживаність ризобій на поверхні насіння, що, у свою чергу, дасть змогу проводити обробку посівного матеріалу завчасно [100][101][102]. При цьому враховують фізичні і хімічні властивості полімерів, добираючи найефективніші композиції досліджуваних сполук і агрономічно корисних мікроорганізмів.…”
unclassified